Penerapan Model Pembelajaran Discovery Learning Sebagai Upaya Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPA Terapan - Hesty Sukmasari (FKIP Universitas Palangka Raya, 2022)
This study aims to determine the effect of applying the Discovery Learning learning model to improving student learning outcomes in class X Catering A SMK N 1 Purwosari and to find out how to increase student learning outcomes through the application of the Discovery Learning learning model to students in class X Catering A SMK N 1 Purwosari . This research is a Classroom Action Research (CAR) with a cycle model that is carried out repeatedly and continuously. The subjects of this study were 21 students in class X Tata Catering A, and the object was the application of the Discovery Learning learning model. This research consists of 3 cycles, each cycle begins with planning, action, observation and ends with reflection, to improve action at the next cycle stage. Based on the results of the analysis carried out that the application of the Discovery Learning learning model can improve learning outcomes in Applied Science Subjects for class X Catering A Students at SMK N 1 Purwosari. There is planning, action, observation and reflection that is carried out consistently in Classroom Action Research, so that there is an increase in learning outcomes in each cycle that is carried out, starting from cycle 1 to cycle 3. The increase in learning outcomes can be seen from the increase in the percentage of student learning completeness from the student's initial value ie from 58.09% to 90.4%.